Celebrate diversity - Razak, Dzulkifli Abd (2010)
HEADGEARS have never made so much news as a symbol of intolerance and ignorance. American Sikhs are protesting at the stigmatisation of their faith because of a new United States security policy to screen turbans. Some cartoonists made headlines by creatively ransforming similar headgears into bombs. One of them, a Dane, was recognised by German Chancellor Angela Merkel for freedom of expression”. A conservative daily reportedly deemed it as “probably the most explosive appointment of her chancellorship so far”. So it is not surprising that last month Merkel led a charge against multiculturalism.